Management model for the logistics and competitiveness of SMEs in the city of Barranquilla (2019)
In Colombia, small and medium-sized enterprises (SMEs) are the most powerful engines of economic development, since they generate a high volume of jobs in the national territory, while diversifying productive, commercial, and service activities. In order to propose a model for logistics management as a component for the competitiveness of SMEs, a qualitative study is proposed that will allow us to collect from a structured review of recent literature, identifying the elements to be taken into account for logistics management in order to provide timely support and open space for continuous improvement. The proposed model is structured in six main blocks: characterization of processes according to the activity of the SME, external factors of influence, internal factors of influence, feeding of information, monitoring and control of operations, and feedback between support areas. The above elements have been analyzed and suggested taking into account the specific aspects of SMEs in the country, and taking into account the peculiarities of these small productive cells.